DESAIN PEMBELAJARAN SEKOLAH DASAR BERBASIS KEARIFAN LOKAL DI KAWASAN PERTAMBAKAN KABUPATEN SIDOARJO - Wachidah, Kemil; Wardana, Mahardika Darmawan Kusuma (Jurnal Pendidikan Dasar, 2018)
This study aims to produce a design of learning based on local wisdom at elementary school in Sidoarjo District aquaculture area. As is known from the analysis of children's learning problems in farming areas, that enthusiasm for learning is low, meaningless learning for the coastal environment situation. The research method uses research & development to produce the design of elementary school in the pond area. The result is a learning design that adapts the material topics according to the local advantages of aquaculture, and the development of learning media from pond algae.